Optimal trade and environmental policies in a polluted small open economy - Gallegos, Alberto (Estudios Económicos de El Colegio de México, 2006)
Using a pollution-trade general equilibrium model, I investigate the theoretical relationship between trade and environmental policies and their welfare effects in a perfectly competitive small open economy, facing trade and pollution distortions. Pollution does harm consumers but does not affect the productivity of neighboring firms and is generated as a by-product of the production process through the industrial use of a pure intermediate input. The final tradeable good and the intermediate input are produced with a constant return to scale technology where non-tradeable primary factors of production are offered inelastically. In this framework there are three instrument considered: a tariff on a final good, a pollution tax and a tariff on the imports of the pollution-creating intermediate input.